High orientation of long chain branched poly (lactic acid) with enhanced blood compatibility and bionic structure. Issue 5 (20th January 2016) - Li, Zhengqiu; Ye, Lin; Zhao, Xiaowen; Coates, Phil; Caton‐Rose, Fin; Martyn, Michasel
Abstract: Highly oriented poly (lactic acid) (PLA) with bionic microgrooves was fabricated through solid hot drawing technology for further improving the mechanical properties and blood biocompatibility of PLA. In order to enhance the melt strength and thus obtain high orientation degree, long chain branched PLA was prepared at first through a two‐step ring‐opening reaction during processing. Linear viscoelasticity combined with branch‐on‐branch model was used to predict probable compositions and chain topologies of the products, and it was found that the molecular weight of PLA increased and topological structures with star like chain with three arms and tree‐like chain with two generations formed during reactive processing, and consequently draw ratio as high as1200% can be achieved during the subsequent hot stretching. With the increase of draw ratio, the tensile strength and orientation degree of PLA increased dramatically. Long chain branching and orientation could significantly enhance the blood compatibility of PLA by prolonging clotting time and decreasing platelet activation. Microgrooves can be observed on the surface of the oriented PLA which were similar to the intimal layer of blood vessel, and such bionic structure resulted from the formation of the oriented shish kebab‐like crystals along the draw direction. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1082–1089, 2016.